Empowering JPC Volunteers with Education and Assistance on Behavioral Factors to Prevent HIV/AIDS Transmission in Bandung, West Java Indonesia - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Intan Silviana Mustikawati; Sukardi Sukardi; Erwin Panigoro; Ade Heryana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The present study reports the newest comprehensive study on pandemic era for the Infectious Disease acquired Immunodeficiency Syndrome (AIDS), caused by the Human Immunodeficiency Virus (HIV) the number of people living with HIV/AIDS (ODHA) continues to grow, this needs to be balanced with efforts to prevent the transmission of HIV/AIDS. The JPC Foundation (Jakarta Plus Center) is one of the important entry points for the community to reach out and educate on the treatment and prevention of HIV/AIDS transmission in Bandung, West Java Indonesia. This study aims to determine the factors associated with HIV/AIDS transmission prevention behavior in HIV/AIDS sufferers in Bandung and Cirebon, West Java Indonesia who are within the reach of the JPC Foundation in 2022. This type of research was quantitative, with cross sectional, the study population was visitors to VCT clinics at shelters with a sample size of 85 respondents. The sampling technique uses accidental sampling. The research was conducted from May to November 2022 with univariate (average) and bivariate (chi-square) data analysis. Univariate results showed that HIV/AIDS prevention behavior was not good 78%, adult age> 25-49 (57.5%), secondary education 50.5%, risky work 69%, good knowledge 57%, negative motivation 62%, positive attitude 69%, negative family support 63%. Bivariate results show that there is a relationship between education (p=0.024), employment (p=0.002), OR=6.057, motivation (p=0.001), OR=7.221, family support (p=0.00) OR=7.778 with behavior prevention of HIV/AIDS transmission at the JPC Foundation shelter in Bandung. For VCT clinics to further improve counseling and education services, for volunteers and cadres who reach out to patients or families of people living with HIV/AIDS (ODHA) to provide more support and assistance, also for the community not to discriminate against ODHA because they have HIV/AIDS.